2011
DOI: 10.1038/labinvest.2010.186
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of treatment with transglutaminase inhibitor cystamine on the severity of inflammation in a rat model of inflammatory bowel disease

Abstract: Inflammatory bowel disease (IBD) represents a socially and clinically relevant disorder, characterized by intestinal chronic inflammation. Cystamine (CysN) is a multipotent molecule with healthy effects and, moreover, it is an inhibitor of transglutaminases (TGs), including the TG type 2 (TG2), an enzyme with pleiotropic functions, involved in different pathways of inflammation and central in the pathogenesis of some human disorders as the IBD. Our aim was to evaluate the effect of CysN in an IBD rat model. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 47 publications
(42 reference statements)
1
18
0
Order By: Relevance
“…For instance, using 2,4,6-trinitrobenzenesulfonic acid-induced colitis as a model of inflammatory bowel disease in rats, it was demonstrated that cystamine treatment markedly diminished colitis-associated inflammation including reduced mucosal proinflammatory cytokine expression. 60 Likewise, cysteamine-mediated inhibition of transglutaminase activity was shown to limit the severity and progression of experimental autoimmune encephalomyelitis, a model of multiple sclerosis in mice. 61 Thus, inhibiting transglutaminase function may be beneficial in limiting a wide array of inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, using 2,4,6-trinitrobenzenesulfonic acid-induced colitis as a model of inflammatory bowel disease in rats, it was demonstrated that cystamine treatment markedly diminished colitis-associated inflammation including reduced mucosal proinflammatory cytokine expression. 60 Likewise, cysteamine-mediated inhibition of transglutaminase activity was shown to limit the severity and progression of experimental autoimmune encephalomyelitis, a model of multiple sclerosis in mice. 61 Thus, inhibiting transglutaminase function may be beneficial in limiting a wide array of inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Cystamine is a TG inhibitor that has been widely used in animal models to study the role of TG (2,7,9,10). In the present study, to examine the role of TG2 in mediating vascular properties, cystamine (40 mg·kg Ϫ1 ·day Ϫ1 ) was delivered to WT and eNOS Ϫ/Ϫ mice for 4 wk using osmotic infusion pumps.…”
Section: Enos Regulates Tg2 Externalization and Activity In Haecmentioning
confidence: 99%
“…Transglutaminases (TGases) are a widely distributed family of enzymes that modify proteins through the hydrolytic deamination or transamidation of the carboxamide moiety of glutamine residues on proteins . Several lines of evidence link TGases with inflammation and hypertension . Initial evidence that TGase contributes to hypertension came from studies showing that cystamine, a transglutaminase inhibitor, reduced blood pressure in the spontaneously hypertensive rat .…”
Section: Introductionmentioning
confidence: 99%
“…15 Several lines of evidence link TGases with inflammation and hypertension. [16][17][18][19][20][21] Initial evidence that TGase contributes to hypertension came from studies showing that cystamine, a transglutaminase inhibitor, reduced blood pressure in the spontaneously hypertensive rat. 22 More recently, we showed that circulating TGase activity is significantly elevated in women with preeclampsia and in an experimental model of preeclampsia in mice.…”
mentioning
confidence: 99%